2002
DOI: 10.1177/1368430202005002539
|View full text |Cite
|
Sign up to set email alerts
|

Differential Association of Uniquely and Non Uniquely Human Emotions with the Ingroup and the Outgroup

Abstract: According to Leyens et al.'s (2000) theory, intergroup discrimination involves a differential appraisal of the ingroup's and the outgroup's uniquely human characteristics. Four experiments investigated how emotions that are considered uniquely (i.e. secondary emotions) and non uniquely (i.e. primary emotions) human (Demoulin et al., 2001a) are differentially associated with the ingroup and the outgroup. Using the Implicit Association Task (IAT) we found a stronger association of ingroup names with uniquely hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0
10

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 139 publications
(82 citation statements)
references
References 23 publications
5
67
0
10
Order By: Relevance
“…Leyens and colleagues (2001), for example, found that Canarians (i.e., inhabitants of the Canary islands, and seen as a lowstatus group) attributed fewer secondary emotions to mainland Spanish people (high-status group) to the same extent as the mainland Spanish WE ARE HUMAN, THEY ARE NOT 81 people did to them. Similar results were obtained in several independent studies using a variety of methods (e.g., Demoulin et al, 2005;Paladino et al, 2002;Paladino & Vaes, 2009;Rodriguez et al, 2011; but see Rohmann, Niedenthal, Brauer, Castano, & Leyens, 2009). These results led researchers to conclude that status differences between groups were not a necessary variable for subtle forms of dehumanisation to occur, nor was the dehumanisation of the other group a one-way bias in which only the dominant derogated the dominated.…”
Section: Relations Moderating Outgroup Dehumanisationsupporting
confidence: 76%
See 1 more Smart Citation
“…Leyens and colleagues (2001), for example, found that Canarians (i.e., inhabitants of the Canary islands, and seen as a lowstatus group) attributed fewer secondary emotions to mainland Spanish people (high-status group) to the same extent as the mainland Spanish WE ARE HUMAN, THEY ARE NOT 81 people did to them. Similar results were obtained in several independent studies using a variety of methods (e.g., Demoulin et al, 2005;Paladino et al, 2002;Paladino & Vaes, 2009;Rodriguez et al, 2011; but see Rohmann, Niedenthal, Brauer, Castano, & Leyens, 2009). These results led researchers to conclude that status differences between groups were not a necessary variable for subtle forms of dehumanisation to occur, nor was the dehumanisation of the other group a one-way bias in which only the dominant derogated the dominated.…”
Section: Relations Moderating Outgroup Dehumanisationsupporting
confidence: 76%
“…All in all, these studies verify the postulated interpretation given to the previous ''association '' experiments (Boccato et al, 2007;Leyens et al, 2001;Paladino et al, 2002): People preferentially associate their group with secondary emotions because such a link shows their humanity. When outgroup members try to do the same, expressing uniquely human emotions, they provoke negative behavioural reactions.…”
Section: We Are Human They Are Not 67supporting
confidence: 75%
“…The most general essence is the human one, and, because groups are ethnocentric, it means that their group is perceived as more human, and less bestial, than outgroups (Leyens et al, 2000. A series of studies have shown that ingroup members associate ''uniquely human" emotions (e.g., affection, contempt) faster with their ingroup than with outgroups (e.g., Boccato, Cortes, Demoulin, & Leyens, 2007;Paladino et al, 2002). People also attribute more uniquely human emotions to the ingroup than to outgroups (e.g., Cortes, Demoulin, RodriguezTorres, Rodriguez-Perez, & Leyens, 2005;Leyens et al, 2001).…”
Section: Infra-humanizationmentioning
confidence: 99%
“…Así, Paladino et al (2002) usaron una adaptación del Test de Asociación Implícita (IAT, Greenwald y Banaji, 1995; Greenwald, McGhee, y Schwartz, 1998) para comprobar si las personas tienen asociados más fuertemente los sentimientos al endogrupo que al exogrupo. Concretamente, Paladino et al (2002) desarrollaron cuatro estudios en los que pidieron a los participantes que clasificaran una serie de palabras que aparecían en la pantalla de un ordenador tan rápido como les fuera posible. Tras varios ensayos de práctica, se les presentó dos tipos de tareas, una congruente y otra incongruente.…”
Section: Dos Formas De Deshumanización: Animalización Y Mecanizaciónunclassified
“…De forma importante, los autores mostraron que este patrón de resultados no sólo aparece con minorías estigmatizadas y grupos de bajo estatus (norte-africanos) sino que también se observa con otros exogrupos no estigmatizados. Así, Paladino et al (2002) comprobaron que los participantes también asociaron los nombres del endogrupo (belgas francófonos) con los sentimientos en mayor medida que los del exogrupo (belgas flamencos). Tal y cómo subrayan los autores, de forma diferente al colectivo norte-africano, el grupo constituido por los belgas flamencos no sólo no es un colectivo minoritario sino que además tienen un estatus mayor que los belgas francó-fonos.…”
Section: Dos Formas De Deshumanización: Animalización Y Mecanizaciónunclassified